Are Online Sources for Identifying Evidence-Based Practices Trustworthy? An Evaluation. (October 2015) - Test, David W.; Kemp-Inman, Amy; Diegelmann, Karen; Hitt, Sara Beth; Bethune, Lauren
The use of evidence-based practices has become a focus in education since the No Child Left Behind Act of 2001 and the Individuals with Disabilities Education Act reauthorization of 2004 required using practices based on scientific research to improve student outcomes. Although many teachers may not have the time or expertise to evaluate the research base for these practices, the prevalence of Internet resources has increased their access to such information. However, web sites differ in type and quality of information provided. The purpose of this study was to examine the trustworthiness of web sites claiming to disseminate evidence-based practices in the area of special education or related services. Of the 47 web sites identified, approximately 57% met the criteria for trust or trust with caution, and 43% were labeled do not trust . Implications for practice and future research are discussed.